Kecerdasan Buatan Dalam Novel Hujan Karya Tere Liye - Nuvita Nur Hayati; Eva Dwi Kurniawan (Simpati, 2024)
Artificial intelligence technology in the industrial era 4.0 provides innovative breakthroughs and can be applied in various sectors of life. Artificial intelligence is also often found in literary works. The purpose of this study is to determine the use of artificial intelligence technology in the novel Hujan by Tere Liye. The method used in this research is to use a hermeneutic approach, which provides an interpretation of the text. Based on the results of analysis and discussion, there are several artificial intelligence technologies contained in the novel, including 1) Robots, 2) Cars, 3) Smart Hotels, 4) Metal Earrings found both in direct descriptions and dialog between characters.